Silicon-carbon negative electrode material and preparation method thereof

Through gas-solid magnesium thermal reduction method and carbon coating technology, the silicon volume expansion problem of the negative electrode material of lithium-ion battery is solved, the cycle stability and charging and discharging efficiency of the battery are improved, and the performance of lithium-ion battery with high energy density and long life is achieved. .

CN119263253AInactive Publication Date: 2025-01-07HEFEI GUOXUAN HIGH TECH POWER ENERGY

Patent Information

Application Number
CN202411038302.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The volume expansion of the existing lithium-ion battery negative electrode material, silicon, during charging and discharging, causes the material to powder and fall off, which cannot meet the needs of high energy density and long cycle life.

Method used

The porous silicon negative electrode material was prepared by gas-solid magnesium thermal reduction method, and the silicon-carbon matrix composite material was filled and coated through asphalt/toluene solution impregnation and vapor-phase deposition carbon coating technology to alleviate the volume expansion effect and prevent the formation of SEI film.

Benefits of technology

The cycle stability of the active material and the first charge and discharge efficiency of lithium-ion batteries have been significantly improved, and the physical and chemical properties and electrochemical properties of the batteries have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263253A_ABST
    Figure CN119263253A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon negative electrode material and a preparation method thereof, and relates to the technical field of lithium ion battery negative electrode materials. A preparation method of a silicon-carbon negative electrode material comprises the following steps: S1, reacting metal magnesium with silicon monoxide in an inert atmosphere at normal pressure and high temperature to obtain an initial product; performing acid pickling, water washing and drying on the primary product to obtain a secondary product; and crushing, grading and demagnetizing the secondary product to obtain the porous silicon negative electrode material. S2, dipping the porous silicon negative electrode material in an asphalt mixed solution, stirring, drying, and performing high-temperature carbonization to obtain a silicon-carbon matrix composite material; and S3, carrying out vapor deposition carbon coating on the silicon-carbon matrix composite material, cooling, and screening to obtain the silicon-carbon negative electrode material. The negative electrode material provided by the invention has excellent physical and chemical properties and electrochemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a silicon-carbon negative electrode material and a preparation method thereof. Background Art

[0002] In recent years, with the rapid popularization and development of portable electronic devices, electric vehicles, etc., traditional graphite negative electrodes can no longer meet the current market demand for high energy density and long cycle life, and there is an urgent need to find the next generation of lithium-ion battery negative electrode materials. Compared with carbon-based negative electrode materials, silicon is an alloyed lithium-intercalation material with a theoretical lithium-intercalation capacity of up to 4200mAh / g. It is rich in resources, safe and non-toxic, and is the most promising lithium-ion battery negative electrode material. However, in the prior art, silicon produces volume expansion (~380%) during the charging and discharging process, resulting in material pulverization, shedding and other defects. Therefore, it is necessary to modify the material to buffer the negative impact of its volume expansion, so as to give full play to the electrochemical properties of the active material and improve its cycle stability, which is a topic that needs to be solved urgently. Summary of the invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a silicon-carbon negative electrode material and a preparation method thereof.

[0004] The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0005] S1. Under normal pressure, high temperature and inert atmosphere, magnesium metal reacts with silicon dioxide to obtain a primary product; the primary product is acid-washed, water-washed and dried to obtain a secondary product; the secondary product is crushed, classified and demagnetized to obtain a porous silicon negative electrode material;

[0006] S2, immersing the porous silicon negative electrode material in an asphalt mixed solution, stirring, drying, and high-temperature carbonizing to obtain a silicon-carbon matrix composite material;

[0007] S3. The silicon-carbon matrix composite material is subjected to vapor deposition carbon coating, cooling, and screening to obtain a silicon-carbon negative electrode material.

[0008] The present invention firstly adopts a relatively mild gas-solid magnesium thermal reduction method, which reduces the heat release of the reaction, controls the size of silicon grains, avoids the agglomeration of magnesium oxide into larger particles and the increase of byproduct magnesium silicate, reduces the damage of the material structure, and is conducive to maintaining a uniform nanoporous structure after subsequent selective pickling; then, the porous silicon is impregnated with asphalt / toluene solution, and carbon is used to fill part of the porous silicon pores, which is similar to the same structure of nano-silicon embedded in a porous carbon network, and can alleviate the volume effect of silicon embedded lithium. The carbon material has a buffering effect on the expansion of the nano-silicon active material; finally, a vapor-deposited carbon coating layer is used to achieve the purpose of uniformly coating the carbon layer on the outside, avoiding the generation of a large amount of SEI film due to the contact between the active material and the electrolyte. The entire process is simple and clear, easy to implement, and shows good physical and chemical properties and electrochemical properties in the battery performance test, and the cycle stability and first charge and discharge efficiency of the active material are greatly improved.

[0009] Preferably, in S1, magnesium vapor is obtained from metallic magnesium at normal pressure and high temperature.

[0010] Preferably, in said S1, the high temperature is 700-950°C.

[0011] Preferably, in the S1, the mass ratio of metallic magnesium to silicon 2 oxide is (1-35):(40-300).

[0012] Preferably, in S1, the detergent used for pickling is a mixed solution of 37% HCl solution and 49% HF solution in a volume ratio of (5-7):1.

[0013] The detergent used in the pickling of the present invention is a mixed acid which can not only wash away the MgO generated after the reaction but also etch the corresponding silicon-oxygen components so as to obtain relatively pure porous silicon.

[0014] Preferably, in the S1, the average particle size D50 of silicon oxide is 1-10 μm, and the particle size of metal magnesium is 200-240 mesh.

[0015] Controlling the average particle size of silicon oxide and the particle size of magnesium metal within a certain range can prevent magnesium oxide from agglomerating into larger particles and the increase of by-product magnesium silicate, reduce material structure damage, and help maintain a uniform nanopore structure after subsequent selective pickling.

[0016] Preferably, in S2, the asphalt mixed solution is an asphalt / toluene solution, and the preparation method of the asphalt mixed solution comprises: dissolving petroleum asphalt in 15wt% toluene and centrifuging for 2-8min, taking the supernatant and mixing it with 10wt% toluene to obtain an asphalt / toluene solution.

[0017] Asphalt / toluene solution is used to impregnate porous silicon, and carbon is used to fill part of the porous silicon pores, which is similar to the same structure of nano-silicon embedded in a porous carbon network. It can alleviate the volume effect of silicon embedded with lithium, and the carbon material also has a buffering effect on the expansion of nano-silicon active materials.

[0018] More preferably, in the S2, the mass ratio of petroleum asphalt, 15wt% toluene, and 10wt% toluene is 1:(4-6):2.

[0019] Preferably, in S2, the high temperature carbonization comprises carbonization at 600-800° C. for 0.5-2 h in an argon atmosphere.

[0020] Controlling the carbonization temperature and time of high-temperature carbonization within a certain range is conducive to complete carbonization, so that carbon can fill part of the pores of porous silicon and alleviate the volume effect caused by lithium embedding in silicon.

[0021] Preferably, in the above S3, the vapor deposition carbon coating includes transferring the silicon-carbon matrix composite material into a CVD deposition furnace and first introducing argon gas to evacuate the furnace; then introducing argon gas at an intake rate of Q1, introducing carbon precursor gas at an intake rate of Q2, and heating the furnace at a heating rate of 2 to 15°C / min to a carbonization temperature of 700 to 1300°C for high-temperature carbonization.

[0022] The present invention adopts vapor deposition carbon coating to achieve the purpose of uniformly coating the carbon layer on the outside, thereby avoiding the generation of a large amount of SEI film due to the contact between the active material and the electrolyte.

[0023] More preferably, in said S3, Q1 is 0.05 to 1.2 L / min; Q2 is 2 to 10 L / min.

[0024] Controlling the gas inlet rates of argon gas and carbon precursor gas within a certain range helps to ensure uniform coating of the outer carbon layer.

[0025] More preferably, in S3, the carbon precursor gas is at least one of methane, ethane, propane, ethylene, propylene and acetylene.

[0026] More preferably, in said S3, the sieving is performed through a 325-mesh sieve, and the sieve residue is taken.

[0027] The present invention also provides a silicon-carbon negative electrode material, which is prepared by the above preparation method.

[0028] The beneficial effects of the present invention are:

[0029] The present invention firstly adopts a relatively mild gas-solid magnesium thermal reduction method, which reduces the heat release of the reaction, controls the size of silicon grains, avoids the agglomeration of magnesium oxide into larger particles and the increase of byproduct magnesium silicate, reduces the damage of the material structure, and is conducive to maintaining a uniform nanoporous structure after subsequent selective pickling; then, the porous silicon is impregnated with asphalt / toluene solution, and carbon is used to fill part of the porous silicon pores, which is similar to the same structure of nano-silicon embedded in a porous carbon network, and can alleviate the volume effect of silicon embedded lithium. The carbon material has a buffering effect on the expansion of the nano-silicon active material; finally, a vapor-deposited carbon coating layer is used to achieve the purpose of uniformly coating the carbon layer on the outside, avoiding the generation of a large amount of SEI film due to the contact between the active material and the electrolyte. The entire process is simple and clear, easy to implement, and shows good physical and chemical properties and electrochemical properties in the battery performance test, and the cycle stability and first charge and discharge efficiency of the active material are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a cross-sectional SEM image of the silicon-carbon negative electrode material PC / Np-Si after argon ion beam cutting in Example 2 of the present invention.

[0031] Figure 2 This is the XRD diagram of the silicon-carbon negative electrode material PC / Np-Si in Example 2 of the present invention. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is described in detail through specific embodiments.

[0033] Unless otherwise specified, the materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources.

[0034] Example 1

[0035] A method for preparing a silicon-carbon negative electrode material comprises the following steps:

[0036] S1. Gas-solid magnesium thermal reduction method: 35.0 g of silicon oxide (D50 is 4.94 μm) is evenly spread on a 325-mesh stainless steel wire mesh with a thickness of 0.50 cm, 19.1 g of 240-mesh magnesium is evenly spread on the bottom of a graphite crucible with a thickness of 0.25 cm, silicon oxide and magnesium are divided into two layers, upper and lower, and placed in a tubular furnace. Silicon oxide and magnesium are in the same reaction space but do not contact each other; argon gas is introduced into the tubular furnace at a gas flow rate of 2 L / min to drive out oxygen for 30 min, argon gas is continuously introduced at a gas flow rate of 0.5 L / min, and the temperature is increased at 5 ° C / min. The temperature was raised to 850°C at a rate, kept at that temperature for 6 hours, and naturally cooled to obtain a primary product (p-SiO); a mixed solution of 37% HCl solution and 49% HF solution in a volume ratio of 6:1 was used as an acid washing detergent, and the cooled primary product (p-SiO) was acid washed with 200g of the acid washing detergent, and the acid washing process was carried out by magnetic stirring for 6 hours, and then washed and filtered, and finally the material on the filter paper was placed in a vacuum drying oven at 60°C for 12 hours to obtain a secondary product; the secondary product was crushed, classified, and demagnetized to obtain a porous silicon negative electrode material (Np-Si);

[0037] S2, asphalt / toluene solution impregnation: 10g petroleum asphalt (ZL250M) was dissolved in 15wt% toluene and centrifuged for 4min, 20g of the supernatant was mixed with 10wt% toluene to obtain an asphalt / toluene solution, 5g of porous silicon negative electrode material (Np-Si) was placed in a flask of asphalt / toluene solution under vacuum conditions, immersed and stirred for 30min, nitrogen was introduced until atmospheric pressure was reached, the flask stopper was opened and the solution was dried overnight while nitrogen was still flowing to obtain P / Np-Si; P / Np-Si was ground in a mortar and pestle and transferred to a tube furnace, heated to 700℃ at a heating rate of 10℃ / min in an argon atmosphere and carbonized for 1h to obtain a silicon-carbon matrix composite material (Np-SiC); the mass ratio of petroleum asphalt, 15wt% toluene, and 10wt% toluene was 1:5:2;

[0038] S3. Vapor deposition carbon coating: The silicon-carbon matrix composite material (Np-SiC) is transferred into a CVD deposition furnace, and argon is introduced at an intake rate of 15 L / min to evacuate for 40 minutes; then argon is introduced at an intake rate of 1.2 L / min, and acetylene is introduced at an intake rate of 2 L / min, and the temperature is increased at a heating rate of 5°C / min to a carbonization temperature of 800°C for high-temperature carbonization for 2 hours, and the furnace is naturally cooled and sieved with 325 mesh to obtain a silicon-carbon negative electrode material (PC / Np-Si).

[0039] Example 2

[0040] A method for preparing a silicon-carbon negative electrode material comprises the following steps:

[0041] S1. 35.0 g of silicon dioxide (D50 is 4.94 μm) is evenly spread on a 325-mesh stainless steel wire mesh with a thickness of 0.50 cm. 10 g of magnesium metal with a 240-mesh mesh is evenly spread on the bottom of a graphite crucible with a thickness of 0.25 cm. Silicon dioxide and magnesium metal are divided into two layers, upper and lower, and placed in a tubular furnace. Silicon dioxide and magnesium metal are in the same reaction space but do not contact each other. Argon gas is introduced into the tubular furnace at a gas flow rate of 2 L / min to drive out oxygen for 30 min, and argon gas is continuously introduced at a gas flow rate of 0.5 L / min. The temperature is raised to 40 ° C. / min at a heating rate of 5 ° C. / min. 850℃, keep warm for 6h, and cool naturally to obtain the primary product (p-SiO); a mixed solution of 37% HCl solution and 49% HF solution in a volume ratio of 6:1 is used as an acid washing detergent, and the cooled primary product (p-SiO) is acid washed with 200g of the acid washing detergent, and the acid washing process adopts magnetic stirring for 6h, and then washed and filtered, and finally the material on the filter paper is placed in a 60℃ vacuum drying oven for 12h to obtain a secondary product; the secondary product is crushed, classified, and demagnetized to obtain a porous silicon negative electrode material (Np-Si);

[0042] S2. Dissolve 10g of petroleum asphalt (ZL250M) in 15wt% toluene and centrifuge for 4min, take 20g of the supernatant and mix it with 10wt% toluene to obtain an asphalt / toluene solution, put 5g of porous silicon negative electrode material (Np-Si) into a flask of asphalt / toluene solution under vacuum conditions, immerse and stir for 30min, introduce nitrogen until atmospheric pressure is reached, open the stopper of the flask and dry the solution overnight while nitrogen is still flowing to obtain P / Np-Si; grind P / Np-Si in a mortar and pestle and transfer to a tube furnace, heat to 700℃ in an argon atmosphere at a heating rate of 10℃ / min and carbonize for 2h to obtain a silicon-carbon matrix composite material (Np-SiC); the mass ratio of petroleum asphalt, 15wt% toluene, and 10wt% toluene is 1:5:2;

[0043] S3. Transfer the silicon-carbon matrix composite material (Np-SiC) into a CVD deposition furnace, introduce argon at an intake rate of 15 L / min to evacuate for 40 min; then introduce argon at an intake rate of 1.2 L / min, introduce acetylene at an intake rate of 2 L / min, increase the temperature to a carbonization temperature of 800 °C at a heating rate of 5 °C / min, carry out high-temperature carbonization for 2 h, cool naturally, and sieve with 325 mesh to obtain a silicon-carbon negative electrode material (PC / Np-Si).

[0044] Example 3

[0045] A method for preparing a silicon-carbon negative electrode material comprises the following steps:

[0046] S1. 35.0 g of silicon dioxide (D50 is 4.94 μm) is evenly spread on a 325-mesh stainless steel wire mesh with a thickness of 0.50 cm. 19.1 g of magnesium metal with a 240-mesh thickness is evenly spread on the bottom of a graphite crucible with a thickness of 0.25 cm. Silicon dioxide and magnesium metal are divided into two layers, upper and lower, and placed in a tubular furnace. Silicon dioxide and magnesium metal are in the same reaction space but do not contact each other. Argon gas is introduced into the tubular furnace at a gas flow rate of 2 L / min to drive out oxygen for 30 min, and argon gas is continuously introduced at a gas flow rate of 0.5 L / min. The temperature is raised at a heating rate of 5 ° C / min. to 800°C, keep warm for 6 hours, and cool naturally to obtain a primary product (p-SiO); a mixed solution of 37% HCl solution and 49% HF solution in a volume ratio of 6:1 is used as an acid washing detergent, and the cooled primary product (p-SiO) is acid washed with 200g of the acid washing detergent, and the acid washing process adopts magnetic stirring for 6 hours, and then washed and filtered, and finally the material on the filter paper is placed in a vacuum drying oven at 60°C for 12 hours to obtain a secondary product; the secondary product is crushed, classified, and demagnetized to obtain a porous silicon negative electrode material (Np-Si);

[0047] S2. Dissolve 10g of petroleum asphalt (ZL250M) in 15wt% toluene and centrifuge for 4min, take 20g of the supernatant and mix it with 10wt% toluene to obtain an asphalt / toluene solution, put 5g of porous silicon negative electrode material (Np-Si) into a flask of asphalt / toluene solution under vacuum conditions, immerse and stir for 30min, introduce nitrogen until atmospheric pressure is reached, open the stopper of the flask and dry the solution overnight while nitrogen is still flowing to obtain P / Np-Si; grind P / Np-Si in a mortar and pestle and transfer to a tube furnace, heat to 700℃ in an argon atmosphere at a heating rate of 10℃ / min and carbonize for 2h to obtain a silicon-carbon matrix composite material (Np-SiC); the mass ratio of petroleum asphalt, 15wt% toluene, and 10wt% toluene is 1:5:2;

[0048] S3. Transfer the silicon-carbon matrix composite material (Np-SiC) into a CVD deposition furnace, introduce argon at an intake rate of 15 L / min to evacuate for 40 min; then introduce argon at an intake rate of 1.2 L / min, introduce acetylene at an intake rate of 2 L / min, increase the temperature to a carbonization temperature of 800 °C at a heating rate of 5 °C / min, carry out high-temperature carbonization for 2 h, cool naturally, and sieve with 325 mesh to obtain a silicon-carbon negative electrode material (PC / Np-Si).

[0049] Example 4

[0050] A method for preparing a silicon-carbon negative electrode material comprises the following steps:

[0051] S1. 35.0 g of silicon dioxide (D50 is 4.94 μm) is evenly spread on a 325-mesh stainless steel wire mesh with a thickness of 0.50 cm. 19.1 g of magnesium metal with a 240-mesh thickness is evenly spread on the bottom of a graphite crucible with a thickness of 0.25 cm. Silicon dioxide and magnesium metal are divided into two layers, upper and lower, and placed in a tubular furnace. Silicon dioxide and magnesium metal are in the same reaction space but do not contact each other. Argon gas is introduced into the tubular furnace at a gas flow rate of 2 L / min to drive out oxygen for 30 min, and argon gas is continuously introduced at a gas flow rate of 0.5 L / min. The temperature is raised at a heating rate of 5 ° C / min. to 900°C, keep warm for 6 hours, and cool naturally to obtain a primary product (p-SiO); a mixed solution of 37% HCl solution and 49% HF solution in a volume ratio of 6:1 is used as an acid washing detergent, and the cooled primary product (p-SiO) is acid washed with 200g of the acid washing detergent, and the acid washing process adopts magnetic stirring for 6 hours, and then washed and filtered, and finally the material on the filter paper is placed in a vacuum drying oven at 60°C for 12 hours to obtain a secondary product; the secondary product is crushed, classified, and demagnetized to obtain a porous silicon negative electrode material (Np-Si);

[0052] S2. Dissolve 10g of petroleum asphalt (ZL250M) in 15wt% toluene and centrifuge for 4min, take 20g of the supernatant and mix it with 10wt% toluene to obtain an asphalt / toluene solution, put 5g of porous silicon negative electrode material (Np-Si) into a flask of asphalt / toluene solution under vacuum conditions, immerse and stir for 30min, introduce nitrogen until atmospheric pressure is reached, open the stopper of the flask and dry the solution overnight while nitrogen is still flowing to obtain P / Np-Si; grind P / Np-Si in a mortar and pestle and transfer to a tube furnace, heat to 700℃ under an argon atmosphere at a heating rate of 10℃ / min and carbonize for 1h to obtain a silicon-carbon matrix composite material (Np-SiC); the mass ratio of petroleum asphalt, 15wt% toluene, and 10wt% toluene is 1:5:2;

[0053] S3. Transfer the silicon-carbon matrix composite material (Np-SiC) into a CVD deposition furnace, introduce argon at an intake rate of 15 L / min to evacuate for 40 min; then introduce argon at an intake rate of 1.2 L / min, introduce acetylene at an intake rate of 2 L / min, increase the temperature to a carbonization temperature of 800 °C at a heating rate of 5 °C / min, carry out high-temperature carbonization for 2 h, cool naturally, and sieve with 325 mesh to obtain a silicon-carbon negative electrode material (PC / Np-Si).

[0054] Comparative Example 1

[0055] The difference between Comparative Example 1 and Example 1 is that the asphalt / toluene solution impregnation in step S2 is not performed, and other conditions remain unchanged, as follows:

[0056] A method for preparing a silicon-carbon negative electrode material comprises the following steps:

[0057] S1. 35.0 g of silicon dioxide (D50 is 4.94 μm) is evenly spread on a 325-mesh stainless steel wire mesh with a thickness of 0.50 cm. 19.1 g of magnesium metal with a 240-mesh thickness is evenly spread on the bottom of a graphite crucible with a thickness of 0.25 cm. Silicon dioxide and magnesium metal are divided into two layers, upper and lower, and placed in a tubular furnace. Silicon dioxide and magnesium metal are in the same reaction space but do not contact each other. Argon gas is introduced into the tubular furnace at a gas flow rate of 2 L / min to drive out oxygen for 30 min, and argon gas is continuously introduced at a gas flow rate of 0.5 L / min. The temperature is raised at a heating rate of 5 ° C / min. to 900°C, keep warm for 6 hours, and cool naturally to obtain a primary product (p-SiO); a mixed solution of 37% HCl solution and 49% HF solution in a volume ratio of 6:1 is used as an acid washing detergent, and the cooled primary product (p-SiO) is acid washed with 200g of the acid washing detergent, and the acid washing process adopts magnetic stirring for 6 hours, and then washed and filtered, and finally the material on the filter paper is placed in a vacuum drying oven at 60°C for 12 hours to obtain a secondary product; the secondary product is crushed, classified, and demagnetized to obtain a porous silicon negative electrode material (Np-Si);

[0058] S2. The porous silicon negative electrode material (Np-Si) is transferred into a CVD deposition furnace, and argon is introduced at an intake rate of 15 L / min to evacuate for 40 minutes; then argon is introduced at an intake rate of 1.2 L / min, and acetylene is introduced at an intake rate of 2 L / min, and the temperature is increased at a heating rate of 5 ° C / min to a carbonization temperature of 800 ° C for high-temperature carbonization for 2 hours, and naturally cooled, and sieved with 325 mesh to obtain a silicon-carbon negative electrode material (PC / Np-Si).

[0059] Comparative Example 2

[0060] The difference between Comparative Example 2 and Example 1 is that step S3 of vapor deposition carbon coating is not performed, and other conditions remain unchanged, as follows:

[0061] A method for preparing a silicon-carbon negative electrode material comprises the following steps:

[0062] S1. 35.0 g of silicon dioxide (D50 is 4.94 μm) is evenly spread on a 325-mesh stainless steel wire mesh with a thickness of 0.50 cm. 19.1 g of magnesium metal with a 240-mesh thickness is evenly spread on the bottom of a graphite crucible with a thickness of 0.25 cm. Silicon dioxide and magnesium metal are divided into two layers, upper and lower, and placed in a tubular furnace. Silicon dioxide and magnesium metal are in the same reaction space but do not contact each other. Argon gas is introduced into the tubular furnace at a gas flow rate of 2 L / min to drive out oxygen for 30 min, and argon gas is continuously introduced at a gas flow rate of 0.5 L / min. The temperature is raised at a heating rate of 5 ° C / min. to 900°C, keep warm for 6 hours, and cool naturally to obtain a primary product (p-SiO); a mixed solution of 37% HCl solution and 49% HF solution in a volume ratio of 6:1 is used as an acid washing detergent, and the cooled primary product (p-SiO) is acid washed with 200g of the acid washing detergent, and the acid washing process adopts magnetic stirring for 6 hours, and then washed and filtered, and finally the material on the filter paper is placed in a vacuum drying oven at 60°C for 12 hours to obtain a secondary product; the secondary product is crushed, classified, and demagnetized to obtain a porous silicon negative electrode material (Np-Si);

[0063] S2. Asphalt / toluene solution impregnation: 10 g of petroleum asphalt (ZL250M) was dissolved in 15 wt% toluene and centrifuged for 4 min. 20 g of the supernatant was mixed with 10 wt% toluene to obtain an asphalt / toluene solution. 5 g of porous silicon negative electrode material (Np-Si) was placed in a flask containing the asphalt / toluene solution under vacuum conditions and immersed and stirred for 30 min. Nitrogen was introduced until atmospheric pressure was reached. The stopper of the flask was opened and the solution was dried overnight while nitrogen was still flowing to obtain P / Np-Si. P / Np-Si was ground in a mortar and pestle and transferred to a tubular furnace. The temperature was increased to 700°C at a heating rate of 10°C / min in an argon atmosphere and carbonized for 1 h to obtain a silicon-carbon negative electrode material (Np-SiC). The mass ratio of petroleum asphalt, 15 wt% toluene, and 10 wt% toluene was 1:5:2.

[0064] The specific surface area and D of the negative electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 and the commercial product (BSO-1 silicon-based material product) were tested. 50 ; The negative electrode materials prepared in the above Examples 1 to 4, Comparative Examples 1 to 2, and the commercial product (BSO-1 silicon-based material product) were used to prepare negative electrode sheets, which were assembled into lithium-ion batteries with positive electrode sheets and separators, and their first charge specific capacity, first coulomb efficiency, and capacity retention rate after 200 cycles at 0.5C were tested. The test results are shown in Table 1.

[0065] Table 1

[0066]

[0067] From the performance comparison results of Examples 1 to 4, Comparative Examples 1 to 2 and commercial products in Table 1, it can be seen that the lithium-ion battery assembled from the negative electrode material prepared by the present invention has excellent first charge specific capacity, first coulomb efficiency, and capacity retention rate after 200 cycles at 0.5C, among which the material performance in Example 2 is the best. The present invention improves the first charge and discharge efficiency and capacity retention rate compared with commercial products through structural design and the introduction of coating process, indicating that the negative electrode material of the present invention inhibits the volume expansion of nano-silicon particles embedded in lithium through material structure design, hinders the direct contact between electrolyte and silicon, and effectively improves the first coulomb efficiency and cycle capacity retention rate of the finished product.

[0068] In summary, the negative electrode material provided by the present invention has excellent physicochemical properties and electrochemical properties, and the active material has good cycle stability and high initial charge and discharge efficiency.

[0069] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: S1. Under normal pressure, high temperature and inert atmosphere, magnesium metal reacts with silicon dioxide to obtain a primary product; the primary product is acid-washed, water-washed and dried to obtain a secondary product; the secondary product is crushed, classified and demagnetized to obtain a porous silicon negative electrode material; S2, immersing the porous silicon negative electrode material in an asphalt mixed solution, stirring, drying, and high-temperature carbonizing to obtain a silicon-carbon matrix composite material; S3. The silicon-carbon matrix composite material is subjected to vapor deposition carbon coating, cooling, and screening to obtain a silicon-carbon negative electrode material.

2. The preparation method according to claim 1, characterized in that: In the above-mentioned S1, the detergent used for pickling is a mixed solution of 37% HCl solution and 49% HF solution in a volume ratio of (5-7):

1.

3. The preparation method according to claim 1, characterized in that: In the S1, the average particle size D50 of silicon oxide is 1-10 μm, and the particle size of metal magnesium is 200-240 mesh.

4. The preparation method according to claim 1, characterized in that: In the S2, the asphalt mixed solution is an asphalt / toluene solution, and the preparation method of the asphalt mixed solution includes: dissolving petroleum asphalt in 15wt% toluene and centrifuging for 2-8min, taking the supernatant and mixing it with 10wt% toluene to obtain an asphalt / toluene solution.

5. The preparation method according to claim 1, characterized in that: In the S2, the high temperature carbonization includes carbonization at 600-800° C. for 0.5-2 h in an argon atmosphere.

6. The preparation method according to claim 1, characterized in that: In the S3, the vapor deposition carbon coating includes transferring the silicon-carbon matrix composite material into a CVD deposition furnace and first introducing argon gas to evacuate it; then introducing argon gas at an intake rate of Q1, introducing carbon precursor gas at an intake rate of Q2, and heating the temperature at a heating rate of 2 to 15°C / min to a carbonization temperature of 700 to 1300°C for high-temperature carbonization.

7. The preparation method according to claim 6, characterized in that: Q1 is 0.05~1.2L / min; Q2 is 2~10L / min.

8. A silicon-carbon negative electrode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparing silicon oxide (SiOx) / carbon (C) composite materials and prepared silicon carbon cathode materials for lithium ion battery

    CN102593426A

  • Porous silicon-based composite anode material for lithium ion battery and preparation method and application

    CN105070894A

  • Nitrogen-doped porous nanosheet silicon carbon composite material and preparation method and application thereof

    CN110474034A

  • High-performance lithium ion battery graphite negative electrode material and preparation method thereof

    CN111333064A

  • Nano hollow porous silicon material as well as preparation method and application thereof

    CN111960423A

Cited By

  • Preparation method of silicon-carbon negative electrode material and silicon-carbon negative electrode material

    CN120039887A

  • A preparation method of silicon-carbon negative electrode material and silicon-carbon negative electrode material

    CN120039887B